Effectiveness of Plants Fiber Impregnated with Green Nanoparticles for Water Disinfection - Abu Dalo, M.; Jaradat, A.; Al-Rawashdeh, N.; Albiss, B. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
In this study, Titanium Dioxide nanoparticles (TiO2 NP) were synthesized using a green hydrothermal method and then mixed with pristine pomegranate peel extract (PPP) to develop a nanocomposite medium (PPP-TiO2). The medium was fully characterized by SEM, DLS and XRD. Biological activity was evaluated by well diffusion method, Microbial Inhibition Concentration (MIC), Minimum Bactericidal Concentration (MBC), growth curve profiling and live/dead cell assay against Staphylococcus aureus (gram positive), Pseudomonas aeruginosa, and Escherichia coli (gram negative). The antimicrobial activity of the nanocomposite medium (PPP-TiO2) was 1.5 times higher compared to PPP or TiO2-NP alone, with higher antibacterial effect against gram positive strains (MIC90 of 189.1, MIC50 of 101.2, MBC 200 µg/mL). These results reveal that the fabricated medium has potential for use in water disinfection.